2021
DOI: 10.3390/w13213114
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Streamflow under Climate Change in the Zambezi River Basin of Southern Africa

Abstract: The Zambezi River basin is the fourth largest basin in Africa and the largest in southern Africa, comprising 5% of the total area of the continent. The basin is extremely vulnerable to climate change effects due to its highly variable climate. The purpose of this study was to evaluate the impact of climate change on streamflow in one of the sub-basins, the Kabombo basin. The multi- global climate model projections were used as input to the Soil Water Assessment Tool (SWAT) hydrological model for simulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…The flow regime estimated for the ungauged catchments using the novel integrated approach shows that the hydropower potential is likely somewhat reduced for the future period. The results agree with the findings that the streamflow under RCP 4.5 may be less than the streamflow under the baseline [54,55]. The findings are also within predictions where different combinations of climate change and water use showed that the relative impacts are quite different across the whole Zambezi River basin [56,57].…”
Section: Discussionsupporting
confidence: 89%
“…The flow regime estimated for the ungauged catchments using the novel integrated approach shows that the hydropower potential is likely somewhat reduced for the future period. The results agree with the findings that the streamflow under RCP 4.5 may be less than the streamflow under the baseline [54,55]. The findings are also within predictions where different combinations of climate change and water use showed that the relative impacts are quite different across the whole Zambezi River basin [56,57].…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, we know and assume that during the operational implementation of the HFS in the UZRB there were countless sources of uncertainty, and different tools and schemes were established in this study to quantify how meteorological and hydrological uncertainty propagate through an operational VEF approach. One of the first adopted techniques that emerged was the utilization of single model realizations as those provided in many previous studies (see for example [3][4][5][6][7][8][9][10][11][12]). Then, multi-ensembles of climate predictions were used to quantify and propagate the meteorological uncertainty through the streamflow forecasts.…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed that the modified version of SWAT improved the simulation of daily streamflow and floodplain development in the Zambezi basin. Several other hydrological models have been satisfactorily calibrated and validated in other sub-basins of the Zambezi with available records (i.e., [7][8][9][10][11][12]). Despite all these modelling efforts in the Zambezi Basin, an operational HFS for the undisturbed flows of the poorly gauged UZRB has yet to be established.…”
Section: Knowledge Gaps and Justification Of The Studymentioning
confidence: 99%
“…The DEM-derived drainage patterns that the model uses to construct small sub-basins that are then divided into smaller sub-basins by a threshold that specifies the required amount of drainage to create a stream [19]. Hydrologic response units (HRU) with unique LULC classes, soil types, and slope classes are created from these small sub-basins [20].…”
Section: Hydrological Modeling Swat Model Selection Set Up and Calibr...mentioning
confidence: 99%